UPAYA MENINGKATKAN HASIL BELAJAR IPS PADA MATERI JENIS PEKERJAAN DENGAN MENGGUNAKAN METODE DEMONSTRASI PADA SISWA KELAS 3 SDN 1 CIKEMBAR SUKABUMI - Eman (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2024)
Based on the problem experienced by the researcher, namely the low learning outcomes of students in class 3 Social Sciences lessons at SD Negeri 1 Cikembar Sukabumi. Encourage researchers to carry out research with the aim of improving student learning outcomes. This research was carried out using a demonstration method in the form of classroom action research in collaboration with colleagues and guided by research procedures. Class 3 students at SDN 1 Cikembar Sukabumi were the subjects of this research with a total of 33 students consisting of 17 female students and 16 male students. After the research was carried out, student learning outcomes increased, namely in the pre-cycle only 14 students completed with a completion percentage of 52%, increasing to 24 students completing and 73% completion percentage, and in cycle 2 it increased again to 31 students completing with a completion percentage of 94. %. Thus, it can be concluded that the use of the demonstration method can improve Social Sciences learning outcomes in class 3 students at SDN 1 Cikembar Sukabumi. This can be seen in the results of cycles 1 and 2 which saw an increase in student learning outcomes and were categorized as very good